Microelectrophoretic Application of Cholinergic Compounds, Protein Oxidizing Agents, and Mercurials to the Chemically Excitable Membrane of the Electroplax - Castillo, J. Del (1972)
Cholinergic compounds, protein oxidizing agents, heavy metal ions, and organic mercurials were microelectrophoretically (or electro-osmotically) applied to the innervated surface of the isolated electroplax of Electrophorus electricus. Phasic potential changes, resembling those observed under similar conditions in frog muscle, followed not only pulses of the common cholinergic drugs, but were also elicited by o-iodosobenzoate, p-chloromercuribenzoate, and Hg(++) ions. These results suggest that cholinergic receptors of both the electroplax and amphibian endplates behave in essentially the same manner. The discrepancies previously observed can be attributed mainly to the different techniques of drug application.